2000
DOI: 10.1128/aac.44.3.756-759.2000
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal, Retinal, and Central Nervous System Foscarnet Concentrations after Rapid Intravenous Administration to Rabbits

Abstract: Retinal, vitreous humor, brain, and cerebrospinal fluid (CSF) foscarnet levels were measured by highperformance liquid chromatography after administration of an intravenous dose of 120 mg/kg of body weight to 32 pigmented rabbits. A pharmacokinetic analysis was done using a two-compartment model. The penetration ratios, defined as ratios of retinal, vitreous humor, brain, and CSF areas under the concentration-time curve from 0 to 2 h were 110% ؎ 1%, 12.3% ؎ 0.7%, 118% ؎ 1%, and 20.2% ؎ 2.2%, respectively. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…34 V ss, ivt and CL ivt values were determined from the available literature on intravitreal drug administra- 35 tion using compartmental models and curve fitting. A simple QSPR model for CL ivt of small molecular 36 weight compounds was obtained with two descriptors: Log D 7.4 and hydrogen bond donor capacity.…”
mentioning
confidence: 99%
“…34 V ss, ivt and CL ivt values were determined from the available literature on intravitreal drug administra- 35 tion using compartmental models and curve fitting. A simple QSPR model for CL ivt of small molecular 36 weight compounds was obtained with two descriptors: Log D 7.4 and hydrogen bond donor capacity.…”
mentioning
confidence: 99%
“…A redução nos índices de morbidade e mortalidade pelo tratamento com PFA nos coelhos inoculados com o BoHV-5 pode também ter sido influenciada pela interferência do fármaco com a replicação do vírus no encéfalo. Estudos anteriores demonstraram que o PFA apresenta uma boa penetração no líquor, atingindo concentrações considerá-veis no SNC de coelhos (López-Cortés et al 2000). Portanto, além de restringir a replicação viral no sítio de entrada, é possível que o fármaco tenha reduzido os níveis da replicação da população de vírus que invadiu o encéfalo, reduzindo assim a carga e disseminação viral no tecido nervoso.…”
Section: Discussionunclassified
“…The drug is negatively charged and its experimental partition coefficient measured at physiological pH is not known. Human trials [63] and animal experiments [64] have shown that foscarnet reaches the CSF to some extent, and this drug has also been shown to cross the BBB easily in animals. Following a single i.v.…”
Section: Drug Physico-chemical Characteristicsmentioning
confidence: 98%